Intellectual Capital in Portuguese tourism sector: study of its impact on organizational performance - Costa, Vânia (2022)
Purpose: According to the literature, the intellectual capital is one of the main competitiveness enhancers of today's companies and a fundamental dimension of organizational performance. This work aims to: (1) identify the added value and the efficiency of intellectual capital in its three dimensions - (i) human capital, (ii) structural capital and (iii) relational capital – in the tourism sector; (2) evaluate its impact on the business performance; (3) analyse the results of VAIC according to the tourism region where the companies are based in. Methodology: Data are draw from Simplified Business Information (IES) based on the Iberian Balance Analysis System (SABI). This study was performed with a sample of sheets and financial reports of 46 951 Portuguese companies in the tourism sector, during the period 2007 to 2016. Findings: VAIC varied slightly between 2007 and 2016. The human capital is the most effective dimension of IC and value creation, which suggests that the tourism sector created substantially more efficient value of IC than the financial component. The HCE presented with a high and statistically significant association with the VAIC. The results indicate the influence that VAIC have on the financial performance of companies. The analysis of the VAIC indicator by regions shows that there are statistically significant differences in the value of the variable VAIC. This indicator show a decrease in all regions in 2016 compared to 2007.The VAIC is higher in the Madeira region. Originality/value: The paper represents a pioneering attempt to understand the relationship between intellectual capital and the firm’s profitability in the Portuguese tourism sector. With this in mind the aim is to provide solid recommendations about the importance of intellectual capital and how it is responsible to assure the sustainable growth of organizations in this sector.